Proteinase inhibitor-inducing activity of the prohormone prosystemin resides exclusively in the C-terminal systemin domain - Dombrowski, James E. (The National Academy of Sciences, 1999)
Prosystemin is the 200-amino acid precursor of the 18-amino acid polypeptide defense hormone, systemin. Herein, we report that prosystemin was found to be as biologically active as systemin when assayed for proteinase inhibitor induction in young tomato plants and nearly as active in the alkalinization response in Lycopersicon esculentum suspension-cultured cells. Similar to many animal prohormones that harbor multiple signals, the systemin precursor contains five imperfect repetitive domains N-terminal to a single systemin domain. Whether the five repetitive domains contain defense signals has not been established. N-terminal deletions of prosystemin had little effect on its activity in tomato plants or suspension-cultured cells. Deletion of the C-terminal region of prosystemin containing the 18-amino acid systemin domain completely abolished its proteinase inhibitor induction and alkalinization activities. The apoplastic fluid from tomato leaves and the medium of cultured cells were analyzed for proteolytic activity that could process prosystemin to systemin. These experiments showed that proteolytic enzymes present in the apoplasm and medium could cleave prosystemin into large fragments, but the enzymes did not produce detectable levels of systemin. Additionally, inhibitors of these proteolytic enzymes did not affect the biological activity of prosystemin. The cumulative data indicated that prosystemin and/or large fragments of prosystemin can be active inducers of defense responses in both tomato leaves and suspension-cultured cells and that the only region of prosystemin that is responsible for activating the defense response resides in the systemin domain.